STILASI BURUNG LUNTUR KASUMBA DENGAN TEKNIK DIGITAL PRINTING PADA BUSANA READY TO-WEAR - Rahayu, Siti Khurriyatunnisa; Katiah, Katiah (Nuansa Journal of Arts and Design, 2021)
Luntur Kasumba (Red-naped Trogon) is a species of bird belonging to the order Trogonidae with the scientific name Harpactes Kasumba which is scattered in the tropical lowland forests of the Great Sunda namely Sumatera, Java, and Kalimantan at an altitude of less than 600 meters above sea level. The source of ideas for making fashion products which are then examined and made in the form of this article comes from the Luntur Kasumba bird which is transformed into a stilation motif and the stylation motif that has been made is applied to textiles using digital printing techniques. The purpose of making articles from the results of the analysis of this fashion product is to elevate the beauty of the Luntur Kasumba bird which is applied to the world of fashion and informed the public in making ready-to-wear clothing, which is further analyzed from the scientific side of the fashion field. The benefit of designing this work is to enhance and develop the writer's creativity in designing fashion by applying the bird stylation of Luntur Kasumba using digital printing techniques and making articles from the analysis of fashion products. The method used in writing the results of the analysis of this fashion product research is Practic-Led Research, which is intended to practice the stapling technique of the Kasunt Luntur bird motif, applying the design of the stylation motif to textiles using digital printing techniques, and is realized in the form of clothing with the addition of fringes as decorative trims. Ready to-Wear clothing made with digital printing techniques with the stylized motif of the Kasumba faded bird is an innovation in preserving the bird species of Indonesia's natural wealth into the world of Fashion. Keywords: Stilation, Luntur Kasumba Bird, Ready to-Wear, Fringes Abstrak Luntur Kasumba (Red-naped Trogon) adalah jenis burung yang tergolong  kedalam ordo Trogonidae dengan nama ilmiah Harpactes Kasumba yang tersebar di hutan dataran rendah tropis Sunda Besar yaitu Sumatera, Jawa, dan Kalimantan pada ketinggian kurang dari 600 meter dari permukaan laut. Sumber ide pembuatan produk busana yang kemudian diteliti dan dibuat dalam bentuk artikel ini berasal dari burung Luntur Kasumba yang diwujudkan menjadi motif stilasi dan motif stilasi yang telah dibuat diaplikasikan pada tekstil menggunakan teknik digital printing. Tujuan pembuatan artikel dari hasil analisis produk busana ini adalah untuk mengangkat keindahan burung Luntur Kasumba yang diterapkan pada dunia fashion dan diinformasikan kepada masyarakat pada pembuatan busana ready to-wear, yang selanjutkan di analisis dari sisi keilmuan bidang busana. Manfaat perancangan karya ini adalah untuk meningkatkan dan mengembangkan kreativitas penulis dalam merancang busana dengan menerapkan stilasi burung Luntur Kasumba mengguanakan teknik digital printing dan membuat artikel dari hasil analisis produk busana. Metode yang digunakan dalam penulisan hasil analisis  dari penelitian produk busana ini yaitu Practic-Led Research, yang dimaksudkan untuk mempraktikan teknik stilasi motif burung Luntur Kasumba, mengaplikasikan desain motif stilasi tersebut pada tekstil menggunakan teknik digital printing, dan diwujudkan dalam bentuk busana dengan penambahan fringes sebagai decorative trims. Busana Ready to-Wear yang dibuat dengan Teknik digital printing dengan motif stilasi burung luntur kasumba merupakan suatu inovasi di dalam melestarikan jenis burung kekayaan alam Indonesia ke dalam dunia Fashion.   Kata Kunci: Stilasi, Burung Luntur Kasumba, Ready to-Wear, Fringes